ISSUES AND CHALLENGES IN RECORD MANAGEMENT: THE ADOPTION OF ERMS - Arif Najmi Bin Bahri; Wan Muhammad Iskandar Zulqarnain Bin Wan Jaaffar; Muhammad Hilman Bin Aris; Nur Farahnisa Binti Mohd Azaham; Wan Nor Syazana Wan Hashim (International Journal of Accounting, Finance and Business, 2022)
The purpose of this study is to give a review of the literature on the issues andchallenges of the adoption of electronic record management system in an organization. In thisreview paper, the existing literature on the acceptance of an electronic record managementsystem in organizations is reviewed. Based on the review, this study concluded that bothtechnological and human are the main challenges that need to be concerned on. Human factorsinclude employee’s readiness, training and resistance to change while technological factorsinvolves the challenges from the technological infrastructure and the integration of newtechnologies. The evaluation will provide future researchers with a comprehensiveunderstanding of the electronic record management system idea and will aid in identifyingresearch gaps. This study will be benefit to the managers or organization in identifying thehindrance factors in ERMS implementation, thus preparing for future strategies in ERMS willbe more practical.